SAHABAT “Sadar Hidup Sehat Bebas Stunting” pada Anak dan Ibu Hamil - Juwita, Noormah; Napu, Mohamad Novaldi; Elisabet, Silvia Gabriela; Fataruba, Fajira Modimbala Murni; Fataruba, Riyanti; Buhang , Mohammad Rikal (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Stunting is currently one of the problems in the world, including Indonesia. This condition is caused by chronic malnutrition and affects children's growth and development. Through this activity, students share their knowledge with the Paku Selatan village community. Methods: This activity was carried out using the following methods: 1). Preparation stage, 2). Implementation stage, 3). Evaluation stage. Results: With the cooperation of the community, cadres and government, this counseling went well and received a good response from the local community who participated in the activity. Conclusions: At the time of community service activities went well. After this socialization program was held, it was obtained to increase knowledge to the Paku Selatan village community about the causes of stunting in children and also interventions that can be carried out in an effort to handle nutrition in preventing stunting.